Propagation measurement on earth-sky signal effects for high speed train satellite channel in tropical region at Ku-band - Al-Jumaily, Abdulmajeed Hammadi Jasim; Sali, Aduwati; Jit Singh, Mandeep Singh; Ismail, Alyani (Hindawi Publishing Corporation, 2015)
Recent advances in satellite communication technologies in the tropical regions have led to significant increase in the demand for services and applications that require high channel quality for mobile satellite terminals. Determination and quantification of these requirements are important to optimize service quality, particularly in the Malaysian region. Moreover, the tests on current satellite propagation models were carried out at temperate regions whose environmental characteristics are much different from those in Malaysia. This difference renders these propagation models inapplicable and irrelevant to tropical regions in general. This paper presents the link characteristics observations and performance analysis with propagation measurements done in tropical region to provide an accurate database regarding rain and power arches supply (PAs) attenuations in the tropics for mobile scenarios. Hence, an extension for improving the performance assessment and analysis of satellite/transmission has been achieved. The Malaysia propagation measurement for mobile scenario (Malaysia-PMMS) enables first-hand coarse estimation and attenuation analysis, because the attenuation resulting from rain and PAs becomes easily amenable for measurement. Parallel to that, the measured attenuation has been compared with that of the simulated output at noise floor level. The underlying analytical tool is validated by measurements specific at tropical region, for dynamic model of mobile satellite links operating at higher than 10 GHz.